Neg-raising interacts with implicatures: The case of doubt - Matticchio, Andrea (Proceedings of the Amsterdam Colloquium, 2024)
The verb doubt is a downward-monotonic attitude predicate. I argue that it should be analyzed as a negated existential modal, and that the inferences it comes with result from the interaction between neg-raising and a possibility implicature. In doing so, I provide a discussion of neg-raising and scalar implicatures arising from one and the same predicate.